Expanding the Indonesian Tarbiyah Movement through TaâÄruf and Marriage - Asyari, Suaidi; Abid, M. Husnul (Al-Jamiah: Journal of Islamic Studies, 2016)
This paper will shed light into the most current phenomena of how Islamist groups create and expand their influence and membership. In view of the Islamists like the Indonesian Tarbiyah movement, Islamisation of society and the state is the ultimate goal to be achieved. Families become the most important means of Islamisation. If all families have been successfully made âIslamicâ, people and the country will follow suit. Preparing the family as the basis of making up society and the establishment of an Islamic state is, therefore, urgent. One of the ways is to match young men and women to get married through taÊ»Äruf or âIslamic introductionâ, which goes against the very popular trend of dating among youths nowadays. In addition to be practiced within Tarbiyah members, marriage is also promoted to the larger public. This group of Islamists use most contemporary modern media to expand their influence. By doing so, this kind of movement will have a tremendous and strong socio-political implication in the long run of Indonesian politics.[Tulisan ini mengkaji fenomena kontemporer tentang bagaimana sebuah kelompok (Gerakan Tarbiyah) membentuk dan meluaskan pengaruh serta keanggotaannya. Kelompok Islam tersebut melihat bahwa Islamisasi masyarakat dan Negara merupakan tujuan utama yang harus dicapai termasuk yang terpenting adalah keluarga. Mereka menganggap bahwa jika unit keluarga sudah menjadi âIslamâ maka masyarakat dan Negara secara otomatis akan mengikutinya. Oleh karena itu keluarga perlu disiapkan sebagai pondasi menuju masyarakat dan Negara yang Islamis. Salah satu cara paling awal adalah dengan memperkenalkan konsep TaÊ»Äruf bagi muda mudi yang ingin menikah, sekaligus sebagai tandingan terhadap konsep âpacaranâ yang saat ini populer. Untuk mempromosikan konsep tersebut ke khalayak yang lebih luas, mereka pun menggunakan media yang paling modern dan masif. Sehingga gerakan mereka tampak kuat implikasinya dalam peta perpolitikan di Indonesia.â] Â